Beyond the sea [videorecording (DVD)] - Spacey, Kevin; Bosworth, Kate, 1983-; Goodman, John, 1952-; Hoskins, Bob (Distributed by Lions Gate Home Entertainment, 2005)
One of America's greatest performers, Bobby Darin lived a rags-to-riches life. He worked his way from shady nightclubs to his dream destination, the Copacabana, where he wowed the crowds with his songs. He was a marvel at singing, songwriting and performing - stealing the hearts of fans everywhere despite the suffering in his own heart.